Efficacy of Ultrasonography in the Diagnosis of Dento-Maxillofacial Swellings among an Urban Population in Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Ultrasonography as an imaging modality in dentistry has been explored in recent years. It is particularly useful in the examination of superficial structures where the use of a high frequency linear transducer produces clearer sonographic images.Aim:To evaluate the efficacy of ultrasound when compared with other known diagnostic examinations.Materials and Methods:This was a prospective cross-sectional study involving patients with maxillofacial swellings in Aminu Kano Teaching Hospital. They were classified as malignant neoplasms, benign cysts, abscesses and infections and lymphoma, according to clinical, radiographic and ultrasound and diagnosis independently. The findings from these methods were then compared to the gold standard histologic findings. Chi-square test, Pearson contingency coefficient, and 2 x 2 contingency table were used in evaluating the diagnostic accuracy, sensitivity as well as the specificity of the examinations.Results:A total of 36 patients comprising 21 males and 15 females with mean age of 34.97 years were recruited. Diagnostic accuracy of ultrasound was 50% in the diagnosis of malignant tumors, 95.8% in benign cystic swellings, 50% in abscesses and infections, and 100% in lymphoma. Significant relationship exists between ultrasonography with histology, clinical and radiographic diagnosis with a contingency coefficient of 0.833, 0.759, and 0.798, respectively. Overall, the accuracy, sensitivity and specificity of ultrasound was 86.1%, 90.3%, and 60%, respectively.Conclusion:Ultrasonography provides accurate imaging of the maxillofacial region and provides information about the pathological characteristic of lesion, its extent, and relationship with the surrounding structures. Inclusion of ultrasonography to the clinical and histopathological examinations increases the accuracy of orofacial swelling diagnosis.